Recovery of red pigments from monascus purpureus FTC 5357 by extraction of fermented solids: Operational conditions and kinetics - Nur Fathin Shamirah, Daud; Farhan, Mohd Said; Chisti, Yusuf; Nur Hidayah, Mat Yasin (Instituto de Tecnologia do Parana, 2021)
Solvent extraction of red pigments from fermented solids is reported. The pigments were produced by solid-state fermentation of oil palm frond (OPF) biomass with the food-safe fungus Monascus purpureus FTC 5357. The effects of extraction solvent and other operational conditions (pH, temperature, agitation rate, contact time) on the recovery of pigments are discussed. The recovery was maximized using aqueous ethanol (60% ethanol by vol) as solvent at pH 6, 30 °C, with an extraction time of 16 h and an agitation rate of 180 rpm. A fermented solids dry mass of 1 g was used for each 160 mL of solvent during extraction. The kinetics of extraction were assessed by fitting the experimental data to different models. Peleg's model proved to be the best for describing solid-liquid extraction of the pigments under the above specified conditions. The highest extraction yield of red pigments under the above specified optimal conditions was 207±6.08 AU g 1 dry fermented solids.